PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN (ENDURANCE) PADA ATLET PUTRA BULUTANGKIS PB.RBC PEKANBARU - Diyanto, Rahmad; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to know the effect of training interval training on endurance of athletes of badminton men’s PB.RBC Pekanbaru. The type of research used is experiment with One Gruop Preetest Posttest Only Desaign design. The population in this study is athletes PB.RBC, the sample in this study is athletes PB.RBC amounted to 6 people. The sampling technique uses the total sampling in which the entire population is sampled. Instrument performed in this study is Bleep Test, which aims to measure the athlete VO2 max. After that the data was processed with statistics, to test the normality with the lilifors test at a significant level of 0.05a. The hypothesis proposed is the effect of training interval training on endurance. Based on t test analysis yield Thitung equal to 7,7 and Ttabel equal to 1,943 mean thitung> ttable. Based on the analysis and statistics, there is an average preetest of 38.7 and average posttest 41.7 with a difference of average value is 3. Thus, there is the effect of training interval training on endurance in athletes of men badminton PB . RBC Pekanbaru.Keywords : Interval Training, Endurance